ANALISA MASALAH HOLE CLEANING PADA EXTENDED REACH DRILLING SUMUR X-11 LAPANGAN Y - Widradjat Aboekasan; Gatari Dewanti (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2017)
The drilling operation is an operation which is very important in the process of exploration and exploitation of oil and gas. Drilling is an important step in the exploration of oil and gas. Drilling aims for oil and gas inside the reservoir can be produced to the surface. The method itself is more advanced starts from vertical drilling, directional drilling to horizontal drilling. In an effort to acquire oil and gas need for innovations in order to optimize the recovery of oil and gas. One innovation that can optimize the acquisition of oil and natural gas are Extended Reach Drilling. Extended Reach Drilling (ERD) is part of a growing directional drilling method because it is supported by tools and a new method in the world of drilling. What differentiate ERD with conventional directional drilling method is a horizontal displacement distance its much larger.This study was conducted to evaluate the execution of ERD in the